A new method for parameters obtaining of Jiles-Atherton hysteresis scalar model - Barbosa R. Mendes, Filomena; Leite, Jean V.; Batistela, Nelson J.; Sadowski, Nelson; Suarez, Fredy M. S. (2016 IEEE Conference on Electromagnetic Field Computation (CEFC), 2016)
The here proposed method is based on rewriting the equations of Jiles-Atherton model to obtain a single non-linear ordinary differential equation used to identify the parameters. This equation involves only the interest variables: H, B with known values, and the model parameters with unknown values. The initial and anhysteretic magnetization curves, and filtering data are not used. The search space of the parameters is not restricted. The model parameters are readily obtainable. To validate the method, experimental data are compared with calculated data.